2020
DOI: 10.1111/apha.13492
|View full text |Cite
|
Sign up to set email alerts
|

Targeting desmosomal adhesion and signalling for intestinal barrier stabilization in inflammatory bowel diseases—Lessons from experimental models and patients

Abstract: Inflammatory bowel diseases (IBD) such as Crohn’s disease (CD) and Ulcerative colitis (UC) have a complex and multifactorial pathogenesis which is incompletely understood. A typical feature closely associated with clinical symptoms is impaired intestinal epithelial barrier function. Mounting evidence suggests that desmosomes, which together with tight junctions (TJ) and adherens junctions (AJ) form the intestinal epithelial barrier, play a distinct role in IBD pathogenesis. This is based on the finding that de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 129 publications
4
55
0
Order By: Relevance
“…Most studies have focused on tight junctional complexes as the primary regulator of permeability, and high-fat or high-sugar intake has been shown to affect these structures (Moreira et al, 2012;Thaiss et al, 2018). Similarly, it has been demonstrated that intestinal desmoglein-2, an adhesion molecule of desmosomes, is required for the maintenance of intestinal barrier and its deficiency cause increased barrier permeability (Schlegel et al, 2020). Our own work has demonstrated the importance of calcium as a regulator of the colonic barrier.…”
Section: Introductionmentioning
confidence: 68%
“…Most studies have focused on tight junctional complexes as the primary regulator of permeability, and high-fat or high-sugar intake has been shown to affect these structures (Moreira et al, 2012;Thaiss et al, 2018). Similarly, it has been demonstrated that intestinal desmoglein-2, an adhesion molecule of desmosomes, is required for the maintenance of intestinal barrier and its deficiency cause increased barrier permeability (Schlegel et al, 2020). Our own work has demonstrated the importance of calcium as a regulator of the colonic barrier.…”
Section: Introductionmentioning
confidence: 68%
“…The intestinal epithelial barrier (IEB) plays an essential role in health and disease. This barrier is maintained by polarized and highly specialized cells, including enterocytes, goblet cells, Paneth cells, enteroendocrine cells and M-cells which line the whole gut lumen [ 1 , 2 , 3 ]. The intercellular space between these cells is sealed by different junctional proteins such as tight junctions, adherens junctions and desmosomes, which together form the apical junctional complex [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…This barrier is maintained by polarized and highly specialized cells, including enterocytes, goblet cells, Paneth cells, enteroendocrine cells and M-cells which line the whole gut lumen [ 1 , 2 , 3 ]. The intercellular space between these cells is sealed by different junctional proteins such as tight junctions, adherens junctions and desmosomes, which together form the apical junctional complex [ 3 ]. Dysregulation of IEB function caused by loss of junctional proteins in the apical junctional complex represents a hallmark in the pathogenesis and perpetuation of inflammatory bowel diseases (IBD) [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intestinal epithelial barrier (IEB) comprises a single continuous layer of cells lining the gastrointestinal tract and serves as the main line of defense against ingested toxins and potentially pathogenic microbes residing in the gastrointestinal wall and lumen ( Vancamelbeke and Vermeire, 2017 ). Tight junctions, adherens junctions, and desmosomes are multi-protein complexes located to the cell membrane of enterocytes that together form a homophilic, tripartite seal from the apical to the basolateral sides, respectively ( Garcia et al., 2018 ; Heinemann and Schuetz, 2019 ; Schlegel et al., 2020 ). Since the original findings in mice ( Cani et al., 2007 , 2008 ), evidence has mounted that obesity is associated with IEB breakdown primarily due to unfavorable shifts in the intestinal microbiota caused by frequent overconsumption of a high-fat diet ( Chakaroun et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%